Active Atrial Function and Atrial Scar Burden After Multiple Catheter Ablations of Persistent Atrial Fibrillation. Issue 2 (31st January 2017) - NÜHRICH, JANA M.; GEISLER, ANNE C.; STEVEN, DANIEL; HOFFMANN, BORIS A.; SCHÄFFER, BENJAMIN; LUND, GUNNAR; STEHNING, CHRISTIAN; RADUNSKI, ULF K.; SULTAN, ARIAN; SCHWARZL, MICHAEL; ADAM, GERHARD; WILLEMS, STEPHAN; et al.
Abstract : Background: Extensive and repeated substrate modification (SM) is frequently performed as an ablation strategy in persistent atrial fibrillation (persAF). The effect of these extended ablation strategies on atrial function has not been investigated sufficiently so far. The purpose was to assess atrial function by cardiac magnetic resonance (CMR) and its association with left atrial (LA) scar burden by electroanatomical voltage‐mapping after multiple persAF ablation procedures. Methods: We included 16 persAF patients who had ≥2 SM procedures and a control group (CG) of 21 persAF patients without prior ablation. CMR was performed in sinus rhythm at least 4 weeks after the last cardioversion. Active left and right (RA) atrial emptying fractions (AEF) as well as peak active left atrial appendage (LAA) emptying velocities were obtained by CMR flow measurements. Furthermore, LA scar burden was quantified on electroanatomical voltage maps by the portion of points with local voltage amplitude <0.2 mV. Results: We found median LA‐AEF to be lower (13 [9–22] vs 32 [26–36] %, P < 0.001) and median LA scar burden to be higher (40 [20–68] vs nine [3–18] %, P < 0.05) in the SM group compared with the CG. Furthermore, a significant correlation was found between mean LA voltage and LA‐AEF (r 2 = 0.62, P < 0.001). No significant differences were detected with respect to median RA‐AEF (41 [28–48] vs 47 [35–50] %, P = 0.43) and median peak LAA emptying velocities (30 [16–40] vs 17 [13–28] cm/s, P = 0.07). Conclusions: Active LA function is preserved but significantly impaired and associated with ablation‐related LA scar burden after multiple extensive persAF ablations.